Serum Low-Density Lipoprotein Cholesterol and Neck Disability Among University Employees: A Cross-Sectional Study - Nathaly Alejandra Rodríguez-Mata; Samuel Olegario Iñiguez-Jimenez; Israel Santiago Vinueza-Fernández; Stephanie Marie Cruz-Pierard (Healthcare, 2026)
Background: Neck pain is a common cause of work-related disability, yet the relationship between serum low-density lipoprotein cholesterol (LDL-C) and neck disability remains uncertain. This study examined whether serum LDL-C was independently associated with neck disability among university employees. Methods: A cross-sectional secondary analysis was conducted using occupational health records from 236 administrative and teaching employees of a private university in Quito, Ecuador. Neck disability was assessed using the Spanish-language Neck Disability Index (NDI). Serum LDL-C was analyzed as a continuous variable (per 10 mg/dL increase). The primary analysis used proportional-odds ordinal logistic regression adjusted for sex, age group, education level, and job position. Model assumptions, multicollinearity, influence, and stability were evaluated. Sensitivity analyses included a three-level ordinal model, multiple linear regression with the continuous NDI score, and nonparametric bootstrap resampling. Results: Mean LDL-C was 112.42 ± 29.09 mg/dL, and 56 participants (23.73%) had LDL-C concentrations ≥ 130 mg/dL. Mild neck disability was the most common category (58.05%), whereas severe disability was uncommon (1.27%). Serum LDL-C was not independently associated with higher neck disability in the adjusted ordinal model (adjusted OR per 10 mg/dL = 0.956; 95% CI, 0.876–1.043; p = 0.309). Sensitivity analyses using alternative-outcome specifications and bootstrap resampling produced consistent findings. Female sex was independently associated with greater disability, whereas no other covariates reached statistical significance. Conclusions: Serum LDL-C was not independently associated with neck disability in this selected occupational population after adjustment for demographic and occupational factors. Prospective multicenter studies incorporating broader cardiometabolic, inflammatory, ergonomic, behavioral, and psychosocial variables are needed to further clarify determinants of neck disability.